Hybrid Cognitive Behavioral Therapy With Interoceptive Exposure for Irritable Bowel Syndrome: A Feasibility Study - Funaba, Misako; Kawanishi, Hitomi; Fujii, Yasushi; Higami, Koyo; Tomita, Yoshitoshi; Maruo, Kazushi; Sugawara, Norio; Oe, Yuki; Kura, Satsuki; Horikoshi, Masaru; Ohara, Chisato; Kikuchi, Hiroe; et al. (Frontiers in Psychiatry, 2021)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder, which severely impairs the quality of life of patients. Treatment of refractory IBS patients is needed, but it is not yet widely available. Therefore, we previously developed a Japanese version of cognitive behavioral therapy with interoceptive exposure (CBT-IE) involving 10 face-to-face sessions to treat refractory IBS patients. To disseminate this treatment of IBS in places where therapists are limited, we further developed a hybrid CBT-IE program with complementary video materials that include psychoeducation and homework instructions so that patients can prepare for face-to-face sessions in advance at home and the session time can be shortened, thereby reducing the burden on both patient and therapist. In this study, we conducted a trial to evaluate the feasibility, efficacy, and safety of the hybrid CBT-IE program for Japanese IBS patients. The study was a single-arm, open-label pilot clinical trial. A total of 16 IBS patients were included in the study and 14 patients completed the intervention, which consisted of 10 weekly individual hybrid CBT-IE sessions. We performed an intention to treat analysis. The primary outcome measure for the efficacy of the intervention was a decrease in the severity of IBS symptoms. The feasibility and safety of the intervention were examined by the dropout rate and recording of adverse events, respectively. The dropout rate of the hybrid CBT-IE was comparable to that of our previous CBT-IE with only face-to-face sessions and no adverse events were recorded. The severity of IBS symptoms within-group was significantly decreased from the baseline to mid-treatment [Hedges' g = −0.98 (−1.54, −0.41)], post-treatment [Hedges' g = −1.48 (−2.09, −0.88)], 3-month follow-up [Hedges' g = −1.78 (−2.41, −1.14)], and 6-month follow-up [Hedges' g = −1.76 (−2.39, −1.13)]. Our results suggest that the hybrid CBT-IE is effective and could be conducted safely. To confirm the effectiveness of the hybrid CBT-IE, it is necessary to conduct a multicenter, parallel-design randomized control trial. Clinical Trial Registration: [https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000041376], identifier [UMIN000036327].